Improving students’ mathematical reasoning and self-efficacy through Missouri mathematics project and problem-solving - Aprisal Aprisal; Agus Maman Abadi (Beta: Jurnal Tadris Matematika, 2018)
[English]: This article aims to elucidate the effectiveness of Missouri mathematics project-problem solving learning (MMP-PS) toward mathematical reasoning ability and self-efficacy. We conducted quasi-experiment research which involves 132 lower secondary school students (age 14-15 years old) as the population. Of the population, 25 students respectively in two classes were selected randomly as experiment class and control class. The experiment class was taught using MMP-PS, and a control class was taught using MMP (Missouri mathematics project learning). Data were analyzed using one sample t-test to examine the effectiveness of MMP-PS and MMP toward mathematics reasoning ability and self-efficacy. The difference of students’ mathematical reasoning and self-efficacy before and after the treatment was analyzed using Manova. The comparison of the effectiveness of MMP-PS and MMP were analyzed through a t-Benferroni test. This article shows that MMP-PS is effective on mathematical reasoning ability and self-efficacy. Meanwhile, MMP is effective on mathematical reasoning ability. The MMP-PS was better than MMP on students’ self-efficacy. Thus, MMP-PS could be utilized in mathematics learning to support students’ mathematical reasoning ability and self-efficacy. Keywords: Missouri mathematics project, Problem solving, Mathematical reasoning, self-efficacy [Bahasa]: Artikel ini bertujuan untuk mendeskripsikan keefektifan pembelajaran missouri mathematics project dengan pendekatan problem solving (MMP-PS) terhadap kemampuan penalaran matematika dan self-efficacy. Penelitian kuasi eksperimen dilaksanakan dengan melibatkan 132 siswa SMP (kisaran umur 14-15 tahun) sebagai populasi. Dipilih secara acak dua kelas yang terdiri dari masing-masing 25 siswa sebagai kelas eksperimen dan kelas kontrol. Kelas eksperimen diajar dengan menggunakan pembelajaran Missouri mathematics project dengan pendekatan problem solving dan kelas kontrol diajar dengan pembelajaran missouri mathematics project (MMP). Data penelitian dianalisis melalui uji satu sampel untuk mengukur keefektifan MMP-PS dan MMP terhadap kemampuan penalaran matematika dan self-efficacy. Perbedaan kemampuan penalaran matematika dan self-efficacy siswa sebelum dan sesudah pembelajaran dianalisis menggunakan uji Manova. Perbandingan keunggulan antara MMP-PS dan MMP menggunakan uji t-Benferroni. Hasil penelitian menunjukkan bahwa MMP-PS efektif ditinjau dari kemampuan penalaran matematika dan self-efficacy. Sementara itu, pembelajaran MMP efektif ditinjau kemampuan penalaran matematika. Pembelajaran MMP-PS lebih unggul dari pembelajaran MMP ditinjau dari self-efficacy siswa. Jadi, MMP-PS bisa digunakan dalam pembelajaran matematika untuk mendukung kemampuan penalaran matematika dan self-efficacy. Kata kunci: Missouri mathematics project, Penalaran matematika, Self-efficacy, Pemecahan masalah